Helminth absence and invasion success of blackchin tilapia (Sarotherodon melanotheron) in Thailand - Suwannarat, Nannaphat; Ribas, Alexis; Miquel, Jordi; Poonlaphdecha, Srisupaph (Frontiers in Veterinary Science, 2025)
IntroductionThis study investigates the helminth absence in the invasive blackchin tilapia (Sarotherodon melanotheron) in Thailand, testing the Enemy Release Hypothesis (ERH). The ERH suggests that invasive species thrive in new habitats due to the lack of natural parasites that control their populations in native environments. The recent introduction of S. melanotheron in Thailand has raised concerns about its ecological and economic impacts.MethodsWe surveyed 164 blackchin tilapia from six different locations in Chumphon Province, Thailand, including the sea, estuary, canal, and shrimp farms, examining them for helminths. Fishermen provided data on the first capture dates in the surveyed areas to determine how long the populations have been established.ResultsNo helminths were detected in any of the examined fish. The absence of parasites was consistent across all surveyed environments, suggesting a lack of parasitic burden in the population.DiscussionThe absence of helminths may contribute to the successful expansion of S. melanotheron in Thailand, supporting the Enemy Release Hypothesis.